Il ripugnante: oltraggio e contraddizione (Lebenswelt. Aesthetics and philosophy of experience., 2021)
For the past twenty years, the relationship between politics, morality and disgust has been resolved into a denunciation of the injustices perpetrated in the name of this emotion. However, no compelling reasons have been brought forward to release the suspicion that the condemnation is merely a corollary of the dominant liberal ideology. I will exemplify this weakness by analysing the theory of disgust proposed by Debra Lieberman and Carlton Patrick in 2018 (§§ 2-3). I will offer a different empirical basis for articulating an adequate answer to the question “what is disgust?” (§4). I will use some acquisitions from philology to exemplify the moral and political scope of disgust (§5). I will propose an “ontological” definition of disgust (§ 6), based on which I will distinguish between disgust and its ethical and political use to justify oppression and discrimination. This use must be replaced by explicating the reasons that justify such oppression and discrimination (§ 7). The fact of not being able to give reasons for such behaviours every time they occur opens up a breach in the direction of a more free and thus more just society.